Integrated approaches for controlling purple blotch of onion for true seed production in Faridpur of Bangladesh - Ahmed, Selim; Quddus, A F M Ruhul; Kamrozzaman, M M; Sarker, Rumpa; Uddin, Md Mohi (Fundamental and Applied Agriculture, 2018)
An experiment was conducted during the Rabi season of 2014–2015 at the farmer’s field of Pearpur, Faridpur Sadar, Faridpur under the supervision of On-Farm Research Division (OFRD), Bangladesh Agricultural Research Institute (BARI), Faridpur to investigate the effective control method of pur- ple blotch of onion during seed production and to develop ecofriendly and cost minimizing approaches for controlling purple blotch. The experiment was conducted using eight treatments viz., T1 = Combination of Iprodione and Mancozeb with Metalaxyl 4 times spray @ 2 g L−1 water each, T2 = Iprodione + Fenamidone with Mancozeb + Propineb + Mancozeb one time alternative spray each @ 2 g L−1 water for 4 times, T3 = Combination of Iprodione and Mancozeb with Metalaxyl 2 times spray @ 2 g L−1 water each + Trichoderma harzianum one time spray @ 50 ml L−1 water + Sanitation (25% removal of infected leaves at 77 DAP), T4 = Trichoderma harzianum two times spray @ 50 ml L−1 water + Combination of Iprodione and Mancozeb with Metalaxyl 1 time spray @ 2 g L−1 water each + Sanitation, T5 = Trichoderma harzianum compost used during final land preparation @ 50 g m−2 plot + T3, T6 = Trichoderma harzianum compost used during final land preparation + Trichoderma harzianum 3 times spray @ 50 ml L−1 water + Sanitation, T7 = Difenoconazole 2 times @ 1 ml L−1 water + combination of Iprodione and Mancozeb with Metalaxyl 2 times spray @ 2 g L−1 water each and T8 = Control. Successful control of purple blotch of onion was achieved by spraying fungicide (chemical plus bio) in treatment T5 followed by T3 and T4 treatment. The highest seed yield was 580 kg ha−1 obtained from the treatment T5 in onion seed crop. The highest benefit: cost ratio (3.92) was calculated from T5 treatment and the lowest from T8 (2.78).